Analysis of the Effectiveness of Women's Protection Laws in the Digital Era - Kurniadi, Wahyu (Siber Nusantara Review & Yayasan Sinergi Inovasi Bersama (SIBER), 2025)
This article analyzes the effectiveness of legal protections for women against online gender-based violence (OGBV) in Indonesia’s digital era. The study uses a normative juridical method by reviewing key regulations, including the Electronic Information and Transactions Law (ITE Law) and the Sexual Violence Crime Law (TPKS Law). The findings reveal that while Indonesia has made significant progress in recognizing and addressing digital violence, various challenges persist. These include ambiguous legal interpretations, limited law enforcement capacity in handling digital evidence, and strong patriarchal cultural influences that hinder victims from seeking justice. Case studies demonstrate fluctuating trends in reported cases, indicating both increased awareness and ongoing systemic barriers. To enhance legal protection, it is crucial to strengthen cross-sector collaboration, improve the technical capabilities of law enforcement, establish specialized agencies, and intensify public education on digital safety. The study emphasizes that effective protection requires not only robust legal frameworks but also consistent implementation and societal support.